PLANNING FOR NATURE-BASED TOURISM IN EAST JAVA: RECENT STATUS OF BIODIVERSITY, CONSERVATION, AND ITS IMPLICATION FOR SUSTAINABLE TOURISM - LUCHMAN HAKIM (ASEAN Journal on Hospitality and Tourism, 2008)
Tourism in Indonesia is now considered a crucial economic sector. However, tourism growth and economic receipts are considered to be low compared to the other Asian countries. One of the problems is believed to be associated with the limited number of competitive destinations to attract the potential market. Therefore enhancing tourism destinations in many places in the Indonesian archipelago is important. An opportunity was found in that this archipelago is home to a huge biodiversity and is endowed with a spectacular landscape. The recent increase in the demand for natural-based tourism provides opportunity for many regions to develop tourism industry. A major obstacle was the lack of understanding of biodiversity and conservation as key elements for such tourism. Therefore the aim of this paper is provide a contextual understanding of natural resources for sustainable tourism planning and development. A case study was done in East Java as a home of high biodiversity and as a luxurious landscape for tourism. We evaluate the recent status of biodiversity and its influence on tourism, and suggest that issues of environmental quality, site-plan design and local people involvement in destination development are the ultimate pillars in establishing competitive and sustainable tourism destination.